The Intestinal Thread of Fate: How the Microbiota Shapes the Story of Liver Disease - Carlo Acierno; Riccardo Nevola; Luca Rinaldi; Ferdinando Carlo Sasso; Luigi Elio Adinolfi; Alfredo Caturano (Livers, 2025)
Metabolic dysfunction–associated steatotic liver disease (MASLD) is a multifactorial condition linked to liver injury, insulin resistance, and disrupted gut–liver interactions. A key aspect of MASLD pathogenesis is the dysfunction of intestinal barriers, including mechanical, immunological, and microbial alterations that amplify liver damage. The disruption of tight junctions and increased intestinal permeability allow microbial products, such as lipopolysaccharides, to enter the bloodstream, triggering liver inflammation via Kupffer cell activation. In MASLD, the gut vascular barrier is also compromised, marked by increased expression of PV-1. Additionally, dysbiosis, driven by high-fat, high-sugar diets, shifts the gut microbiota toward pro-inflammatory species, exacerbating systemic inflammation and intestinal permeability. This imbalance activates Toll-like receptor signaling, which promotes endotoxin-induced liver injury. Gut dysbiosis further impairs lipid metabolism, contributing to hepatic steatosis and MASLD progression. The gut–liver axis plays a critical role, with factors like altered bile acid metabolism and toxic metabolites such as hydrogen sulfide worsening intestinal barrier function and fueling chronic inflammation. This review aims to explore the complex role of the gut–liver axis in MASLD progression, highlighting the mechanisms of intestinal barrier dysfunction, dysbiosis, and microbial contributions to liver injury. It also discusses therapeutic strategies targeting intestinal barriers, including dietary and microbiota-based interventions, while acknowledging the challenges of personalized treatment approaches. Future research should focus on multi-omics technologies and the safety and efficacy of microbiota-targeted therapies in MASLD management.